Upacara Ngusaba Dalem Di Desa Pakraman Bantang Kintamani - Ni Kadek Supadmini; I Made Sukariawan; Ni Made Mahendrayani (Purwadita : Jurnal Agama dan Budaya, 2023)
Religious ceremonies for Hindus in Bali are quite numerous and very varied in remote villages in the Bali area, especially in Bangli Regency, Kintamani District. Bangli Regency is one of the areas that has many traditional communities in which there are customs and institutions as a unique pattern of life. Including in this case, Pakraman Bantang Village located in Kintamani District, Bangli Regency has unique customs and life patterns. This uniqueness can be seen in the many ceremonies carried out by the people of Pakraman Bantang Village such as the Pit Suji ceremony, Kepik Suji, Ngusaba Gede Dangsil Tungguh, Karya Daa Truna and so on. This research is a qualitative research. The results of the study outline related processes, functions and implications  Ngusaba Dalem Ceremony in Pakraman Bantang Kintamani Village